2023
DOI: 10.3390/agronomy13102599
|View full text |Cite
|
Sign up to set email alerts
|

Updates and Prospects: Morphological, Physiological, and Molecular Regulation in Crop Response to Waterlogging Stress

Lu Yang,
Na Li,
Yang Liu
et al.

Abstract: With the frequent occurrence of extreme weather such as typhoons and rainstorms, waterlogging has become one of the most important threats to global crop growth and production. Waterlogging limits plants’ access to oxygen and light, leading to disadvantageous changes in metabolism to disturb plant growth and development. To escape the damage of hypoxia or promote the diffusion of oxygen to submerged organs, plants respond to waterlogging stress by regulating their morphological structure, photosynthesis, respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 207 publications
0
3
0
Order By: Relevance
“…Consequently, under anoxygenic conditions, ARs support and enhance gas diffusion and water and nutrient uptake in plants along and across the roots via air-filled space known as aerenchyma (Steffens and Rasmussen, 2016). Therefore, plants that can quickly form AR under waterlogged conditions are expected to be a better adaptation trait for waterlogging environments (Yang et al, 2023). In the current study, no tested varieties developed AR under control conditions (Figures 5, 6).…”
Section: Waterlogging Tolerance Is Associated With Adventitious Root ...mentioning
confidence: 58%
“…Consequently, under anoxygenic conditions, ARs support and enhance gas diffusion and water and nutrient uptake in plants along and across the roots via air-filled space known as aerenchyma (Steffens and Rasmussen, 2016). Therefore, plants that can quickly form AR under waterlogged conditions are expected to be a better adaptation trait for waterlogging environments (Yang et al, 2023). In the current study, no tested varieties developed AR under control conditions (Figures 5, 6).…”
Section: Waterlogging Tolerance Is Associated With Adventitious Root ...mentioning
confidence: 58%
“…Two hormones namely Abscisic acid (ABA) and ethylene (ET) were identified as key drivers for systemic signaling during water stress ( Hsu et al., 2011 ; TSAI et al., 2014 ). One of the earliest responses to anoxia conditions in plant roots or shoots is the activation of calcium and reactive oxygen species (ROS) signaling cascades and suppression of mitochondrial respiration ( Yang et al., 2023 ). Some of the key players like vacuolar H + /calcium transporter CATION/PROTON EXCHANGER 1 (CAX1) and the RESPIRATORY BURST OXIDASE HOMOLOGs D and F ( RBOHD and RBOHF ) that drive early response during waterlogging have been identified that regulates distinct anoxia response like aerenchyma formation ( Liu et al., 2017 ; Yang et al., 2022 ).…”
Section: Waterlogging Stress In Plantsmentioning
confidence: 99%
“…Overexpression of the ERF transcription factor Sub1A in waterlogging sensitive rice varieties can significantly enhance the waterlogging tolerance of transgenic lines [24,25]. The expression of TaERFVI.1 in wheat is also induced by waterlogging stress [26,27]. Overexpression of TaERFVI.1 can significantly improve the waterlogging tolerance of wheat, but has no adverse effect on yield [27].…”
Section: Introductionmentioning
confidence: 99%